Churchill and Finland : a study in anticommunism and geopolitics - Ruotsila, Markku (Frank Cass, 2005)
Using Winston Churchill's relations with Finland as the case study, this book examines the development of Winston Churchill's anticommunist and geopolitical beliefs and practices, and the conflicts between them.